Final Analysis of Post‐Marketing Surveillance for Avelumab + Axitinib in Patients With Renal Cell Carcinoma in Japan - Norio Nonomura; Taito Ito; Masashi Sato; Makiko Morita; Mie Ogi; Masahiro Kajita; Mototsugu Oya (Cancer Medicine)
ABSTRACT Introduction Avelumab, an anti‐programmed death ligand 1 antibody, was approved in combination with axitinib for curatively unresectable or metastatic renal cell carcinoma (RCC) in Japan in December 2019. Because the pivotal JAVELIN Renal 101 study included a limited number of Japanese patients, post‐marketing surveillance (PMS) was required to evaluate outcomes (safety and effectiveness) in patients with RCC who received avelumab + axitinib treatment in clinical practice in Japan. Materials and Methods We report data from prospective, noncomparative, multicenter, observational PMS in patients with RCC who received ≥ 1 dose of avelumab. Patients were enrolled between December 2019 (date of regulatory approval) and May 2021. The primary objective was to evaluate safety, defined as adverse drug reactions (ADRs) of safety specifications occurring during an observation period of ≤ 52 weeks for each patient. The secondary objective was to evaluate effectiveness, including best overall response and overall survival (OS). Results In total, 328 patients were included in the safety and effectiveness analysis sets. Overall, 173 patients (52.7%) had ADRs of safety specifications of any grade, most commonly thyroid dysfunction (n = 69 [21.0%]), infusion reaction (n = 65 [19.8%]), and hepatic disorders (n = 45 [13.7%]). Objective responses occurred in 118 patients (36.0%), including complete or partial responses in 13 (4.0%) and 105 (32.0%), respectively; the disease control rate was 75.6%. The 12‐month OS rate was 83.7% (95% CI, 78.9%–87.4%). Discussion This PMS confirmed the safety, tolerability, and effectiveness of avelumab + axitinib in patients with RCC in clinical practice in Japan, with a benefit–risk profile comparable to that observed in clinical trials.